Synthesis, Crystal Structure and Magnetic Property of a Sandwich-Like Cyanide-Bridged Fe(III)-Mn(II) Complex - Zhang, Daopeng; Zhao, Zengdian; Chen, Xia (Asian Journal of Chemistry, 2013)
A trinuclear cyanide-bridged Fe(III)-Mn(II) complex has been synthesized with pyridine carboxamide trans-dicyanide iron building block and structurally characterized as trinuclear sandwich-like, in which the two cyanide-containing building blocks acting as a monodentate ligand were coordinated face to face to central Mn(II) ion. Investigation over its magnetic property reveals the antiferromagnetic magnetic coupling between the cyanide-bridged neighboring Fe(III) and Mn(II) ions.